2020
DOI: 10.1017/s0143814x20000288
|View full text |Cite
|
Sign up to set email alerts
|

Race–gender bias in white Americans’ preferences for gun availability

Abstract: We argue that Americans’ policy attitudes on firearm availability are influenced by the identity of the prospective owner. We use an experiment to demonstrate that attitudes towards gun control/availability are influenced by both race and gender; whether subjects are primed to think of African-Americans versus whites or men versus women has a substantial impact on the degree to which they support firearm access. We find that for many white Americans, Black men and white women stand on opposite poles – priming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…This is compounded by the fact that gun rights advocates commonly believe that only law‐abiding citizens obey gun laws, and thus, “if guns are outlawed, only outlaws will have guns” (Wright, 1988, p. 30). Again, such rhetoric evokes racialized imagery due to the racial typification of crime (Pickett et al., 2012), evidenced by the fact that many Americans feel threatened by Black gun ownership but not by White gun ownership (Carlson, 2019; Hayes et al., 2020).…”
Section: The Political Relevance Of Race and Gunsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is compounded by the fact that gun rights advocates commonly believe that only law‐abiding citizens obey gun laws, and thus, “if guns are outlawed, only outlaws will have guns” (Wright, 1988, p. 30). Again, such rhetoric evokes racialized imagery due to the racial typification of crime (Pickett et al., 2012), evidenced by the fact that many Americans feel threatened by Black gun ownership but not by White gun ownership (Carlson, 2019; Hayes et al., 2020).…”
Section: The Political Relevance Of Race and Gunsmentioning
confidence: 99%
“…In practice, the right to bear arms was not always extended to all American residents. Many states issued “Black codes” and regulations that constricted the rights of both free and enslaved Blacks from purchasing and owning guns (Cook & Goss, 2014; Cramer, 1994), in some cases prohibiting Black gun ownership entirely (Hayes et al., 2020). When these codes were eventually labeled unconstitutional, policy makers found subtler ways to limit Black gun ownership, such as banning types of affordable handguns that were most commonly owned by Blacks (Cook & Goss, 2014).…”
Section: The Political Relevance Of Race and Gunsmentioning
confidence: 99%
See 1 more Smart Citation
“…There remains, however, a paucity of evidence about how racial attitudes, net of political factors, might shape this reluctance to share information about gun ownership. In an environment in which gun politics have become deeply racialized and while the face of the federal government was the nation’s first Black President, such a hypothesis is worth testing (Brown, 2013; Carlson, 2020; Filindra and Kaplan, 2016; Hayes, Fortunato, and Hibbing, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These differences in the identities of opioid substance users may be what has caused public opinion and subsequently public policy to support treatment rather than punishment much more than during past drug crises. Past research has shown that associating racial minorities with other policies—from welfare, to the Affordable Care Act (ACA), to gun ownership—may cause white Americans to oppose those policies (e.g., Gilens, 1999 ; Hayes et al, 2020 ; Tesler, 2012 ). The whiter media narrative surrounding the opioid crisis could, in an opposite effect, drive members of the public to support compassionate opioid treatment policies.…”
mentioning
confidence: 99%